2011
DOI: 10.1007/s12031-011-9513-7
|View full text |Cite
|
Sign up to set email alerts
|

Candidate-Gene Approach in Posttraumatic Stress Disorder After Urban Violence: Association Analysis of the Genes Encoding Serotonin Transporter, Dopamine Transporter, and BDNF

Abstract: Posttraumatic stress disorder (PTSD) is a prevalent, disabling anxiety disorder marked by behavioral and physiologic alterations which commonly follows a chronic course. Exposure to a traumatic event constitutes a necessary, but not sufficient, factor. There is evidence from twin studies supporting a significant genetic predisposition to PTSD. However, the precise genetic loci still remain unclear. The objective of the present study was to identify, in a case-control study, whether the brain-derived neurotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 64 publications
3
64
1
Order By: Relevance
“…There are several studies with controversial results of BDNF rs6265 in association with PTSD susceptibility [25] [29]. Our study showed the involvement of BDNF rs6265 in PTSD.…”
Section: Discussionsupporting
confidence: 57%
“…There are several studies with controversial results of BDNF rs6265 in association with PTSD susceptibility [25] [29]. Our study showed the involvement of BDNF rs6265 in PTSD.…”
Section: Discussionsupporting
confidence: 57%
“…In one study, low BDNF serum levels were associated with PTSD, while another reported no relationship to PTSD in victims of urban violence (Valente et al. 2011). However, the Met allele (one and two alleles) of BDNF Val66Met polymorphism may be associated with PTSD severity in veterans (Pivac et al.…”
Section: Introductionmentioning
confidence: 99%
“…During each stage of screening, the literature articles were clearly identified and a consensus could be established. Finally, 6 articles [14,16,17,18,19,26] were selected. Articles in each selection step are shown in online supplementary figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…The related studies were conducted in adults among European (Croatia), Asian (South Korea) and American populations (USA and Brazil). In detail, 3 articles [16,19,26] involved healthy individuals as controls, and another 2 papers [14,17] used people who suffered from the same stress as cases but without PTSD symptoms - 1 article [18 ]contained both types of controls and thus were treated separately as 2 studies. In addition, 2 articles [14,17] examined PTSD participants who were exposed to stress/traumatic events from active duty in the army.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation